(untitled) (Economics and region, 2019)
The tourism industry is considered as one of the leading industries in the field of structural restructuring of the economy, characterized by certain properties and functions. The indicators of the development of the tourist industry of Ukraine are analyzed. The necessity of determining the strategic goal of the tourism business development is substantiated. The prospects for improving the tourism business and improving the efficiency of tourism enterprises are determined, due to the tendency and development of tourism that tourists will choose.